Luke's account of Peter in his strategy of proclaiming a gospel for all people - Parry, DTN (2014)
In his two-volume account of Christian beginnings Luke fills out for already instructed Theophilus Mark’s account of Jesus, and extends it to tell of the bringing of ‘good news’ for all people, offering a tested alternative to the pagan world-view, worthy to be adopted by citizens of the Roman empire. Primarily employing ‘redaction-critical’ methods and seeking narrative patterns with variations within the whole text, we analyse the roles of Peter in the first half of Acts and the influences upon Luke in their making. They portray the pattern of apostolic witness in message, deed and life, and anticipate the extending of the mission to Gentiles, which is taken up in a heroic way by Paul in the second half of Acts. Then analysing Luke’s reshaping of the account of Peter before Easter in his first volume, we show it is done with an eye to how it will be completed in Acts, how Peter will repent from denying Jesus to strengthen his brother apostles and urge repentance on his fellow-Jews. Luke’s captivating narrative is persuasive for its implied reader in the context of the post-apostolic age, that the apostolic kerygma proclaims the divine gift of salvation expected by Israel’s prophets, despite its rejection by much of Judaism. The missions of Paul are to be received as being in harmony with Peter’s. A foundation has been established which will outface Christian rivalries and strengthen believers under persecution. The influence of Luke’s account on other early Christian writers is tested where evidence is available. Luke’s success is that his account became, almost without rival, the canonical New Testament account of Christian beginnings.